Creep properties of single crystal Ni-base superalloys (SX): A comparison between conventionally cast and additive manufactured CMSX-4 materials - Bürger, D.; Parsa, A. B.; Ramsperger, Markus; Körner, Carolin; Eggeler, G. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
The present work compares the microstructures and the creep properties of two types of single crystal Ni-base superalloy CMSX-4 materials (SXs). One was produced by conventional directional solidification Bridgman processing. The other was manufactured by selective electron beam melting (SEBM). The microstructures of the two types of materials are compared with emphasis placed on the large (dendritic/interdendritic regions) and small scale (γ-matrix/γ′-precipitates) microstructural heterogeneities, which characterize SX microstructures and their evolution during processing, heat treatment and creep. It is shown that heat treated SEBM materials have creep properties, which match or even outperform those of conventionally processed SX materials. Creep properties were assessed using a miniature creep test technique where [001] miniature tensile creep specimens were tested in the high temperature/low stress (1050 °C, 160 MPa) and in the low temperature/high stress (850 °C, 600 MPa) creep regimes. The creep behavior is interpreted based on microstructural results, which were obtained using analytical scanning and transmission electron microscopy (SEM and TEM).
CRIS-Team Scopus Importer:2019-07-12
Keywords: Additive manufactured single crystal; Creep; Directionally solidified single crystals; Microstructure; Ni-base single crystal superalloys

Effect of heat treatment on the high temperature fatigue life of single crystalline nickel base superalloy additively manufactured by means of selective electron beam melting - Meid, Carla; Dennstedt, Anne; Ramsperger, Markus; Pistor, Julian; Ruttert, Benjamin; Lopez-Galilea, Inmaculada; Theisen, Werner; Körner, Carolin; Bartsch, Marion (Scripta Materialia, 2019)
The high temperature low cycle fatigue behavior of specimens manufactured from a single crystalline nickel base superalloy processed by selective electron beam melting (SEBM) has been investigated with respect to the effect of different heat treatments. The fatigue lifetime of heat treated material was significantly higher than that of as-built material. Applying hot isostatic pressing (HIP) with an integrated heat treatment resulted in even longer fatigue life. Lifetime limiting crack initiation occurred at interfaces of melting layers, at micro-porosity generated during solidification or, in HIP treated samples, at precipitates which formed at the location of collapsed pores.
Keywords: Low cycle fatigue (LCF); Single crystal superalloy; Selective electron beam melting (SEBM); Hot isostatic pressing (HIP); Microstructure

Impact of hot isostatic pressing on microstructures of CMSX-4 Ni-base superalloy fabricated by selective electron beam melting - Ruttert, B.; Ramsperger, Markus; Mujica Roncery, L.; Lopez-Galilea, I.; Körner, Carolin; Theisen, Werner (Materials and Design, 2016)
Selective electron beam melting (SEBM) is a powder-bed-based additive manufacturing process that was used to produce cylindrical and columnar-grained parts made of Ni-base superalloy CMSX-4 from pre-alloyed and atomized powder. SEBM is characterized by high temperature gradients during solidification, which results in a very fine microstructure that is several orders of magnitude smaller than in conventionally cast material. This opens up new perspectives regarding time-consuming solution heat treatment. Nevertheless, microstructural heterogeneities, such as segregation and porosity, are still present on a much smaller scale, and also the high susceptibility to cracking of this alloy class during welding has to be taken into account. Since the latest generation of hot isostatic presses (HIP) are able to simultaneously heat-treat and eliminate porosity owing to their quenching capability, such a HIP is used in this work. The influence of different HIPing-heat-treatment-strategies with variation of temperature and time at a constant pressure on the SEBM-microstructure was investigated with emphasis primarily on segregation and porosity. The results demonstrate that only a few minutes of solutioning are sufficient to dissolve segregations and to close pores. The initial degree of homogeneity of the SEBM-material is responsible for the short solutioning-time.
Keywords: Additive manufacturing; CMSX-4; Heat treatment; Hip; Hot isostatic pressing; Ni-base superalloy; Porosity; Segregation; Selective electron-beam melting

Microstructure and Mechanical Properties of CMSX-4 Single Crystals Prepared by Additive Manufacturing - Körner, Carolin; Ramsperger, Markus; Meid, C.; Bürger, D.; Wollgramm, P.; Bartsch, M.; Eggeler, Gunther (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2018)
Currently, additive manufacturing (AM) experiences significant attention in nearly all industrial sectors. AM is already well established in fields such as medicine or spare part production. Nevertheless, processing of high-performance nickel-based superalloys and especially single crystalline alloys such as CMSX-4® is challenging due to the difficulty of intense crack formation. Selective electron beam melting (SEBM) takes place at high process temperatures ( 1000 °C) and under vacuum conditions. Current work has demonstrated processing of CMSX-4® without crack formation. In addition, by using appropriate AM scan strategies, even single crystals (SX SEBM CMSX-4®) develop directly from the powder bed. In this contribution, we investigate the mechanical properties of SX SEBM CMSX-4® prepared by SEBM in the as-built condition and after heat treatment. The focus is on hardness, strength, low cycle fatigue, and creep properties. These properties are compared with conventional cast and heat-treated material.

Microstructure of the Nickel-Base Superalloy CMSX-4 Fabricated by Selective Electron Beam Melting - Ramsperger, Markus; Singer, Robert; Körner, Carolin (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2016)
Powder bed-based additive manufacturing (AM) processes are characterized by very high-temperature gradients and solidification rates. These conditions lead to microstructures orders of magnitude smaller than in conventional casting processes. Especially in the field of high performance alloys, like nickel-base superalloys, this opens new opportunities for homogenization and alloy development. Nevertheless, the high susceptibility to cracking of precipitation-hardenable superalloys is a challenge for AM. In this study, electron beam-based AM is used to fabricate samples from gas-atomized pre-alloyed CMSX-4 powder. The influence of the processing strategy on crack formation is investigated. The samples are characterized by optical and SEM microscopy and analyzed by microprobe analysis. Differential scanning calorimetry is used to demonstrate the effect of the fine microstructure on characteristic temperatures. In addition, in situ heat treatment effects are investigated.

Numerical microstructure prediction by a coupled finite element cellular automaton model for selective electron beam melting - Köpf, Johannes; Soldner, Dominic; Ramsperger, Markus; Mergheim, Julia; Markl, Matthias; Körner, Carolin (Computational Materials Science, 2019)
Selective Electron Beam Melting (SEBM) refers to an additive manufacturing process of building near net shaped components layer wise by iteratively melting of metal powder using an electron beam. Due to the preheating of the material and very high scan velocities of the electron beam, the process allows large processing windows defined by different process strategies. This variety enables the adjustment of part properties by, e.g., targeting certain microstructures. However, this variety has its disadvantage in the need for costly trial and error experiments. Therefore, numerical predictions are inevitable in locating promising process parameter combinations. We present the weak coupling of a Finite-Element (FE) model with a cellular automaton (CA) model to predict the microstructure evolution during SEBM. We use an FE model for the computation of the heat input, since the temperature history mainly influences the subsequent microstructure evolution. The FE model provides precomputed temperature fields for our sophisticated CA-based crystal growth model, which successfully predicts bulk material microstructures. The compound is validated by accurately reproducing the microstructure of an additively build cylinder from CMSX-4 powder, a nickel based superalloy. Special emphasize is laid on the accurate prediction of the microstructure both in the shell as well as the core of the cylinder.
Keywords: Crystal growth; Finite element method; Additive manufacturing; Cellular automata; Nickel-base superalloy; Numerical heat solver; High performance computing; Microstructure simulation; Powder bed fusion; Selective electron beam melting

Selective electron beam melting of the single crystalline nickel-base superalloy CMSX-4®: From columnar grains to a single crystal - Körner, Carolin; Ramsperger, Markus (Superalloys 2016: Proceedings of the 13th Intenational Symposium of Superalloys, 2016)
Selective electron beam melting (SEBM) is a powder-bed-based additive manufacturing technology. SEBM offers a great potential to process high performance alloys like intermetallics, e.g. TiAl or FeAl, and Ni-based superalloys, which are hard or non weldable materials with high susceptibility to crack-formation. Especially the high process temperatures during SEBM are beneficial for reducing stresses and warpage. In addition, SEBM works under vacuum which guarantees a perfect protection against contamination. In this contribution, SEBM of the single crystalline nickel-base superalloy CMSX-4®1 is investigated. It is shown that crack formation can be avoided by appropriate processing conditions. Regarding the microstructure, SEBM opens the possibility to tailor the microstructure. Whether a columnar grained or a single crystalline grain microstructure is produced depends on the process strategy used. For the first time it is shown, that it is even possible to produce a single crystalline material by an additive powder bed manufacturing process without any grain selector or a seed crystal. The inherent high cooling rates during SEBM lead to a strong reduction of the length scale of the well-known strong segregations in CMSX-4® to some microns. Therefore, long-time and expensive heat treatments are reduced to minutes for a complete homogenization of the single crystal specimen, even for Re. The specimens produced were investigated by using classical optical-metallography techniques and SEM imaging. Complementary microprobe element mappings and EBSD measurements were performed for a detailed analysis of the microstructure.
Keywords: Additive manufacturing; CMSX-4®; Ni-based superalloys; Powder processing; Selective electron beam melting; Single-crystal

Selektives Elektronenstrahlschmelzen der einkristallinen Ni-Basis Superlegierung CMSX-4 - Ramsperger, Markus (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

Solution Heat Treatment of the Single Crystal Nickel-Base Superalloy CMSX-4 Fabricated by Selective Electron Beam Melting - Ramsperger, Markus; Mujica Roncery, L.; Lopez-Galilea, I.; Singer, Robert; Theisen, Werner; Körner, Carolin (Advanced Engineering Materials, 2015)
Selective electron beam melting (SEBM), which belongs to the additive manufacturing processes, is applied to produce samples from the single crystalline nickel-base superalloy CMSX-4. The influence of the high solidification rates on the microstructure and element distribution is investigated by OM, SEM, DSC, and EMPA. Solution heat treatments at different temperatures and holding times are applied to demonstrate the difference between conventionally cast and SEBM material. The results demonstrate that SEBM is able to produce superalloys with a degree of homogeneity which cannot be realized in conventional processes. Selective electron beam melting (SEBM) manufacturing of CMSX-4 leads to a very fine solidification structure which is two orders of magnitude smaller than in conventional castings (e.g., Bridgman). Microprobe mappings of Re distribution in CMSX-4 can be used to show the differences in homogeneity (a and b). Due to the homogeneity, a solution heat treatment (HT) of 4 min (1320 °C) is already sufficient for homogenization of SEBM CMSX- 4 (c).

Transmission electron microscopy of a CMSX-4 Ni-base superalloy produced by selective electron beam melting - Parsa, Alireza B.; Ramsperger, Markus; Kostka, Aleksander; Somsen, Christoph; Körner, Carolin; Eggeler, Gunther (Metals, 2016)
In this work, the microstructures of superalloy specimens produced using selective electron beam melting additive manufacturing were characterized. The materials were produced using a CMSX-4 powder. Two selective electron beam melting processing strategies, which result in higher and lower effective cooling rates, are described. Orientation imaging microscopy, scanning transmission electron microscopy and conventional high resolution transmission electron microscopy are used to investigate the microstructures. Our results suggest that selective electron beam melting processing results in near equilibrium microstructures, as far as γ′ volume fractions, the formation of small amounts of TCP phases and the partitioning behavior of the alloy elements are concerned. As expected, higher cooling rates result in smaller dendrite spacings, which are two orders of magnitude smaller than observed during conventional single crystal casting. During processing, columnar grains grow in <100> directions, which are rotated with respect to each other. There are coarse γ/γ′ microstructures in high angle boundary regions. Dislocation networks form low angle boundaries. A striking feature of the as processed selective electron beam melting specimens is their high dislocation density. From a fundamental point of view, this opens new possibilities for the investigation of elementary dislocation processes which accompany solidification.
Keywords: Evolution of microstructure; Ingrown dislocations; Ni-base superalloy; Selective electron beam melting; Transmission electron microscopy